Rancang Bangun Model Infrastruktur Transmisi Data Aplikasi E-government pada Level Sinyal Edge Menggunakan IaaS (Infrastructur As A Service) - Dwirgo Sahlinal; Rima Maulini (Politeknik Harapan Bersama, 2018)
The poor cellular signal strength subscription is one of major problem faced by most of the sub-districts in the Lampung province. Poor cellular signal strength subscription has a side effect in Internet transmission data processes both of transmit mode (Tx) and receives mode (Rx). To solve the problem that has been presented, this research proposed a new approach by utilizing Internet Infrastructure as a Service (IaaS) based on Cloud Computing to solve Internet data transmission problems. This research gets a conclusion that Cloud Computing-based Internet Infrastructure as a Service (IaaS) can convert a massive transmission data packets and break it down to a small transmission packet that can be transmitted or received through GSM-EDGE signal level.